Patterning the Asteraceae Capitulum: Duplications and Differential Expression of the Flower Symmetry CYC2-Like Genes - Chen, Jie; Shen, Chu-Ze; Guo, Yan-Ping; Rao, Guang-Yuan (Frontiers in Plant Science, 2018)
There are several types of capitulum in the Asteraceae due to different combinations of florets varying in corolla shape and stamen development. Previous studies have shown that the formation of ray florets on a radiate capitulum may be related to the parallel co-option of CYC2-like genes among independent Asteraceae lineages. The present work tests that hypothesis and attempts to shed lights on the pattern of evolution of the Asteraceae capitulum and floral hetromorphism under the regulation of CYC2-like genes. In this study, the evolutionary history of CYC2-like genes in Asterales was reconstructed and their expression patterns were examined in species representing different capitulum types and several major Asteraceae lineages. To clarify the role of CYC2d clade genes in morphogenesis of ray flowers, overexpression of ClCYC2d was conducted in Chrysanthemum lavandulifolium. Our results show that there are six CYC2-like members in Asteraceae; they are results of five duplication events starting from a single-copy gene in the common ancestor of the Goodeniaceae-Calyceraceae-Asteraceae group and completing before the divergence of the subfamily Carduoideae of Asteraceae. Spatial expression pattern of each of the Asteraceae CYC2-like members is conserved across the family. All the six members contribute to the development of the complexity of a capitulum: To form a ray floret, either CYC2c or CYC2g plays an essential role, while CYC2d represses the development of dorsal corolla lobes and stamens of the floret. In sum, the developmental program of making a ray flower is conserved involving functionally divergent CYC2-like genes. Based on extensive species sampling, this study provides an overview of the mode of regulation of CYC2-like genes that patterns the capitulum architectures and their transitions.